The Effects of Gamification on Restaurant Consumer-Retention - L. Harakal, Kyra; D. Berger, Paul (British Journal of Marketing Studies, 2017)
This paper considers the marketing concept of gamification. This includes most loyalty programs, but, in addition, has tentacles in many other areas of marketing. It is a concept which has been growing rapidly in the marketing field. While a lot has been written about it, there is little quantitative analysis of its impact. In this paper, we perform a statistical analysis using a database of about 1,100 people and several variables, related to the restaurant industry in particular. We consider several hypotheses. One is whether the consumer loyalty engendered by gamification differs by gender. Another is the relationship between customer loyalty engendered by gamification and some restaurant-specific measures, such as frequency of visits to the restaurant, amount of money spent at a restaurant, and the impact of special rewards programs. We also consider which variables are significant in a predictive model with the dependent variable: I would visit a restaurant more often with the presence of as points-based reward program, and several of the earlier-considered variables as independent variables